Engaging the Vulnerabilities of Alzheimers disease: a Care Ethics Perspective (Bangladesh Journal of Bioethics, 2016)
This paper shows that beyond the ethical issues of autonomy and human dignity there some dynamics of vulnerabilities elicited by Alzheimers disease (AD). It therefore underscores how the ethics of care moral lens offers ethically sensitive ways of engaging the individual and social vulnerabilities of associated with AD. Ultimately, the paper highlights some of the social implications of such an approach.